Pemulihan Komunitas Karang Keras Pasca Pemutihan Karang di Amed Bali - Omega Raya Simarangkir; Fredinan Yulianda; Mennofatria Boer (Institut Pertanian Bogor, 2015)
Climate change is now recognized as one of the greatest threats to worldwide coral reefs with one of the most serious and immediate threats of mass coral bleaching associated with increasing sea temperatures. Coral bleaching occurred in a few coral reefs throughout the world in 2010. Coral reef in Amed’s coastal area was the one of the reefs that experienced and affected by coral bleeching incident. This study aims to assess recovery of hard coral community in post-bleaching in 2010. A survey method was used to collect primary data. Data sets also supported by secondary data. This study results were hard coral community recovered in 2013, as its percentage cover increased up to 49.00%. However, macroalgae decreased up to 0.67%. Hard coral recruitment in 2013 increased up to 21 individual/m2.